Risk of post‐gastric bypass surgery hypoglycemia in nondiabetic individuals: A single center experience. Issue 6 (June 2016) - Lee, Clare J.; Wood, G. Craig; Lazo, Mariana; Brown, Todd T.; Clark, Jeanne M.; Still, Christopher; Benotti, Peter
Abstract : Objective: The epidemiology of post‐gastric bypass surgery hypoglycemia (PGBH) is incompletely understood. This study aimed to evaluate the risk of PGBH among nondiabetic patients and associated factors. Methods: A cohort study of nondiabetic patients who underwent Roux‐en‐Y gastric bypass (RYGB) was conducted. PGBH was defined by any postoperative record of glucose < 60 mg/dL, diagnosis of hypoglycemia, or any medication use for treatment of PGBH. Kaplan‐Meier analysis was used to describe PGBH occurrence, log‐rank tests, and Cox regression to examine associated factors. Results: Of the 1, 206 eligible patients, 86% were female with mean age of 43.7 years, mean preoperative BMI of 48.7 kg/m 2, and a mean follow‐up of 4.8 years. The cumulative incidence of hypoglycemia at 1 and 5 years post‐RYGB was 2.7% and 13.3%, respectively. Incidence of PGBH was identified in 158 patients and was associated with lower preoperative BMI ( P = 0.048), lower preoperative HbA1c ( P = 0.012), and higher 6‐month percent of excess body weight loss (%EWL) ( P = 0.001). A lower preoperative HbA1c (HR = 1.73, P = 0.0034) and higher 6‐month %EWL (HR = 1.96, P = 0.0074) remained independently correlated with increased risk for PGBH in multi‐regression analysis. Conclusions: The 5‐year incidence of PGBH among nondiabetic individuals was 13.3% and was associated with a lower preoperative HbA1c and greater weight loss at 6 months following surgery.